Accessory Factors of Cytoplasmic Viral RNA Sensors Required for Antiviral Innate Immune Response - Oshiumi, Hiroyuki; Kouwaki, Takahisa; Seya, Tsukasa (Frontiers in Immunology, 2016)
Type I interferon (IFN) induces many antiviral factors in host cells. RIG-I-like receptors (RLRs) are cytoplasmic viral RNA sensors that trigger the signal to induce the innate immune response that includes type I IFN production. RIG-I and MDA5 are RLRs that form nucleoprotein filaments along viral double-stranded RNA, resulting in the activation of MAVS adaptor molecule. The MAVS protein forms a prion-like aggregation structure, leading to type I IFN production. RIG-I and MDA5 undergo post-translational modification. TRIM25 and Riplet ubiquitin ligases deliver a K63-linked polyubiquitin moiety to the RIG-I N-terminal caspase activation and recruitment domains (CARDs) and C-terminal region; the polyubiquitin chain then stabilizes the two-CARD tetramer structure required for MAVS assembly. MDA5 activation is regulated by phosphorylation. RIOK3 is a protein kinase that phosphorylates the MDA5 protein in a steady state, and PP1α/γ dephosphorylate this protein, resulting in its activation. RIG-I and MDA5 require cytoplasmic RNA helicases for their efficient activation. LGP2, another RLR, is an RNA helicase involved in RLR signaling. This protein does not possess N-terminal CARDs and thus cannot trigger downstream signaling by itself. Recent studies have revealed that this protein modulates MDA5 filament formation, resulting in enhanced type I IFN production. Several other cytoplasmic RNA helicases are involved in RLR signaling. DDX3, DHX29, DHX36, and DDX60 RNA helicases have been reported to be involved in RLR-mediated type I IFN production after viral infection. However, the underlying mechanism is largely unknown. Future studies are required to reveal the role of RNA helicases in the RLR signaling pathway.